Patient-reported outcomes for tofacitinib with and without methotrexate, or adalimumab with methotrexate, in rheumatoid arthritis: a phase IIIB/IV trial. Issue 2 (1st October 2019) - Strand, Vibeke; Mysler, Eduardo; Moots, Robert J; Wallenstein, Gene V; DeMasi, Ryan; Gruben, David; Soma, Koshika; Iikuni, Noriko; Smolen, Josef S; Fleischmann, Roy
Abstract : Objective: To provide the first direct comparison of patient-reported outcomes (PROs) following treatment with tofacitinib monotherapy versus tofacitinib or adalimumab (ADA) in combination with methotrexate (MTX) in patients with rheumatoid arthritis (RA) with inadequate response to MTX (MTX-IR). Methods: ORAL Strategy (NCT02187055 ), a phase IIIB/IV, head-to-head, randomised controlled trial, assessed non-inferiority between tofacitinib 5 mg two times per day monotherapy, tofacitinib 5 mg two times per day+MTX and ADA 40 mg every other week+MTX. PROs assessed included the following: Patient Global Assessment of disease activity (PtGA), Pain, Health Assessment Questionnaire-Disability Index, Functional Assessment of Chronic Illness Therapy-Fatigue and 36-Item Short-Form Health Survey (SF-36) summary and domain scores. Results: Substantial improvements from baseline were reported across all PROs in all treatment arms, which, in the majority, met or exceeded minimum clinically important differences. Compared with tofacitinib monotherapy, tofacitinib+MTX combination treatment conferred significantly greater improvements in PtGA, Pain and SF-36 physical component summary scores at month 6. Statistically or numerically greater improvements were often, but not uniformly, reported for combination treatments compared with tofacitinib monotherapy at other time points. Conclusion: Treatment with tofacitinib+MTX, ADA+MTX and tofacitinib monotherapy resulted in clinically meaningful improvements in PROs in MTX-IR patients with RA. These were comparatively greater with combination treatments versus tofacitinib monotherapy, although differences between treatment arms were small, limiting our ability to confer clinical meaning. Trial registration number: NCT02187055 .